Reform of Healthcare and Pension Systems in Chile (Conclusions for Poland) - Piasecki, Ryszar (Comparative Economic Research. Central and Eastern Europe, 2011)
Health reform in Chile attemps to improve healthcare of the citizens. The authorities of the country managed to combine both the private (ISAPRE) and public systems FONASA). The biggest success was the creation of AUGE (state subsidies for 66 diseases). The unsolved problems are as follows: long waiting lists and shortages of beds in public hospitals, shortage of medical doctors and specialists. As far as the pension reform is concerned Chile was the first state in the world which in 1981 totally privatized the public pension system. Unfortunately, the fruit of changes in Chile is less optimistic (extremely low pensions) than it was initially assumed. According to specialists the only chance for a correct work of the pension system is introduction of the system which would combine two forms, i.e. a state intergenerational agreement and capital system.